DETERMINATION OF ORTHOREXIA NERVOZA IN UNIVERSITY STUDENTS - M. Emel Alphan; Gökhan Dege (Sakarya University, 2021)
Objective: This study was conducted in order to evaluate orthorexia nervosa (ON) tendency of the students of the Department of Nutrition and Dietetics studying at Trakya University according to the variables of gender, age and body mass index (BMI). Method: A total of 125 students (19 males, 106 females) studying in daytime education participated in the study. The research data were collected by the researcher using the "questionnaire method", by interviewing the participants face to face. Socio-demographic characteristics (gender, age, place of residence, etc.) of the participants were determined and their anthropometric measurements were taken. In addition, "Eating Attitude Test (EAT-40)" was used to evaluate eating disorders, "ORTO-15" test to define ON and "Maudsley Obsessive Compulsive Inventory" to evaluate obsessive symptoms. Results: It was determined that male individuals had higher EAT-40 scores than females, while females' ORTO-15 scores and obsessive scores were higher than males (p gt; 0.05). The majority of both males and females (94.7% and 93.4%, respectively) were in the low risk group according to the EAT-40 assessment. It was found that 73.7% of men and 56.6% of women were orthorexic. In the analyzes performed according to age groups, it was found that there was a statistically significant difference in the obsessive score (p lt;0.05). In the correlation analysis performed with the scales, a statistically significant negative correlation was found between the EAT-40 score and the ORTO-15, ORTO-15 and obsessive score (p lt;0.05). Conclusion: In conclusion, it will be beneficial to conduct more comprehensive studies evaluating ON and related factors.